Pengaruh Metode Pengambilan Sampel (Cotton Swab dan Cytobrush) Terhadap Kualitas Preparat Sitologi Oral Exfoliative Pada Pewarnaan Papanicolaou - Almellia, Putri; Ndruru, Ratna Anggun Kristiani; Simanullang, Sara Agnes Julica; Ramadhani, Shaumi Anjani; Lusiana, Diana Intan Gabriella; Setyoningrum, Fransisca Probo (Lembaga Teewan Journal Solutions, 2026)
Exfoliative oral cytology is a non-invasive screening method that supports the early detection of precancerous lesions and oral cavity cancers. The quality of the specimens produced for examination is influenced by preanalytical factors, including the type of sampling device used. This study aims to analyze the effect of using cotton swabs and cytobrushes on the quality of exfoliative oral cytology specimens stained with Papanicolaou using the Liquid-Based Cytology (LBC) method. This laboratory-based experimental study involved 18 healthy participants aged 18–25 years, selected using purposive sampling. Mucosal samples were collected using cotton swabs and cytobrushes, resulting in 36 preparations. All preparations were processed using the LBC method, stained with Papanicolaou stain, and then examined under a microscope to evaluate cell density, distribution, and the clarity of the preparation’s background. Differences in the surface characteristics between the cotton swab and the cytobrush were found to influence the quality of the resulting preparations. The cytobrush was deemed more effective for assessing cell density, whereas the cotton swab provided a cleaner background and better cell distribution. These findings can be considered when selecting sampling tools appropriate for the purpose of oral cytology examinations.